On West Semites in Babylonia during the Chaldean and Achaemenian Periods: An Onomastic Study - Zadok, Ran (1977)
obtainable from Dr. Ran Zadok, 4 Hannasi Street, Pardess Hannah-Karkur, Israel; $22.00.